(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Background: Hypotension during spinal anaesthesia for caesarean section remains a common scenarioin our clinical practice. Certain risk factors play a role in altering the incidence of hypotension. Ephedrinehas been the drug of choice for more than 30 years in the treatment of spinal anesthesia induced maternalhypotension. It has a good safety record, ready availability, and familiarity to most anesthesiologists. Aims: To determine the efficacy and safety of prophylactic bolus dose of 0.5 mg/kg intravenous ephedrinefor the prevention of hypotension during spinal anesthesia for cesarean delivery. Methods: It was designed a randomized, double-blinded study. Patients were randomly allocated intotwo groups: ephedrine group (n=30) and control group (n=30). Intravenous preload of 15 mL/kg lactatedRinger’s solution was given. Shortly after the spinal injection, ephedrine0.5 mg/kg or saline was injectedintravenous for 60 sec. Results: The mean of highestand lowest heart rate in the ephedrine group was higher than those ofcontrol group (p<0.05). There were significant lower incidences of hypotension and nauseaand vomitingin the ephedrine group compared with the control group 11(36.7%) vs. 24(80.0%); 6(20.0%) vs. 17 (56.7%),respectively) (p<0.05). The first rescue ephedrine time in the ephedrine group was significantly longer(14.9±7.1 min vs. 7.9±5.4 min) than that of the control group (p<0.05). Neonatal outcome were similarbetween the study groups. Conclusion: The above findings suggest, the prophylactic bolus dose of 0.5 mg/kg intravenous ephedrinegiven at the time of intrathecal block after a crystalloidfluid preload, plus rescue boluses reduce theincidence of hypotension. JBSA 2018; 31(2): 88-94